2021
DOI: 10.3389/fragi.2021.757080
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Commercial Activity Tracker Based Physical Activity Intervention on Body Composition and Cardiometabolic Health Among Recent Retirees

Abstract: The REACT is a commercial activity tracker based intervention, which primarily aimed to increase physical activity. This study examines the secondary outcomes of the physical activity intervention on body composition and cardiometabolic health indicators. Overall 231 recently retired Finnish men and women [65.2 (SD 1.1) years, 83% women] took part to the study. The participants were randomized into intervention (n = 117) and control (n = 114) groups. The intervention group members used a commercial activity tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…When compared to the non-user controls, this study found that 1-year daily use of an activity tracker did not improve the cardiometabolic health indicators, with the exception of blood pressure reduction. 10 In Tehran, Iran, a further single-blind RCT was conducted with seventy obese or overweight women with MetS who were between the ages of 20 and 50. A normal weight loss diet (NWLD) with 52% -55% ages of 20 and 50.…”
Section: Recent Data From Clinical Trialsmentioning
confidence: 99%
“…When compared to the non-user controls, this study found that 1-year daily use of an activity tracker did not improve the cardiometabolic health indicators, with the exception of blood pressure reduction. 10 In Tehran, Iran, a further single-blind RCT was conducted with seventy obese or overweight women with MetS who were between the ages of 20 and 50. A normal weight loss diet (NWLD) with 52% -55% ages of 20 and 50.…”
Section: Recent Data From Clinical Trialsmentioning
confidence: 99%